ASUPAN ZAT GIZI MAKRO DAN SCREEN TIME BERKORELASI DENGAN STATUS GIZI PADA REMAJA SMAN 1 KRIAN - Annisa Rindy Antika; Cleonara Yanuar Dini (J-KESMAS: Jurnal Kesehatan Masyarakat, 2025)
Nutritional status adolescents is an important indicator in supporting optimal health and growth. Nutritional status is influenced by various factors, including macronutrient intake and screen time. This study aims to determine the relationship between macronutrient intake and screen time with the nutritional status of adolescents at SMAN 1 Krian. The method used in this study was quantitative, with a cross-sectional design, conducted in July-August 2024 with a sample of 103 participants. Data were obtained through 2x24-hour food recall questionnaire interviews and screen time questionnaires, as well as height and weight measurements.. The data analysis technique used was the Pearson Correlation Test. This study showed that 96.1% of adolescents had low carbohydrate intake, 51.5% low protein intake, 64.1% low fat intake, 68% high screen time duration, and 66% normal nutritional status. It was concluded that macronutrient intake (p<0.05) and screen time (p= 0.000; r=0.624) correlated with nutritional status in adolescents at SMAN 1 Krian. Therefore, food intake and screen time duration in adolescents need to be considered to achieve optimal nutritional status.